150 A RARE CASE OF ACIDOSIS-INDUCED DELAYED REVERSIBILITY OF NEUROMUSCULAR BLOCKADE. Issue 1 (1st January 2007) - Sircar, P.; Godkar, D.; Balachandran, J.; Niranjan, S.; Krishnan, P.
Abstract : Introduction: A group of neuromuscular disorders are described to accompany critical illness. Generally, three distinct types of muscle weaknesses are now recognized, namely critical illness polyneuropathy, prolonged neuromuscular blockade, and acute myopathy (with combined use of a glucocorticoid and a neuromuscular blocking drug). Complete quadriplegic paralysis is the most dramatic manifestation of these conditions. We discuss below a case of prolonged neuromuscular blockade, attributable to a rare and relatively unknown cause. Case Report: A 41-year-old lady with advanced AIDS was admitted with Pneumocystis carinii pneumonia. Despite treatment with Bactrim and corticosteroids, the patient rapidly went into respiratory failure (requiring mechanical ventilation) and septic shock with multiorgan dysfunction (predominantly renal tubular acidosis). To achieve adequate oxygenation, a neuromuscular blocking agent was used to achieve synchrony with the ventilator. In view of renal dysfunction, we chose cis-atracurium (the clearance of which is known to be much less affected by renal failure) as the preferred agent. Respiratory status soon improved, the patient's chest radiograph looked better, the A-a gradiant narrowed, and oxygenation improved dramatically. However, the patient's renal failure worsened, with significant metabolic acidosis, and her pH remained around 7.2. After discontinuation of the neuromuscular blocking agent, patient was found to be quadriplegic, with persistent suppression of the train-of-four twitch response to peripheral nerve stimulation, and her muscle strength transiently improved with pyridostigmine. This was puzzling because even with renal dysfunction, we had not expected a prolonged neuromuscular blockade with cis-atracurium. Also, the patient was not sick long enough to fit the criteria of critical illness polyneuropathy. She was on corticosteroids for only 5 days, so steroid myopathy also seemed unlikely. The only caveat that remained was the persistence of severe acidosis, and true enough, as the renal failure resolved and the pH rose to 7.35, the patient recovered from the quadriplegia dramatically and regained normal neuromuscular functions. Conclusion: We are aware of the fact that prolonged neuromuscular blockade (sometimes up to 1 week) can occur in critical care settings with agents such as pancuronium and vecuronium, which produce functionally active 3-hydroxy metabolites that accumulate and persist in the blood in renal failure. It is also important for physicians to know that 'acidosis alone' can prolong the effect of agents such as cis-atracurium, in the absence of other identifiable reasons.